Misuse of medication in adult substance misuse services: a systematic review protocol - Ian Maidment; Rosalind Gittins; Louise Missen (BMJ Open)
Introduction There is a growing concern about the misuse of over the counter (OTC) and prescription only medication (POM) because of the impact on physical and mental health, drug interactions, overdoses and drug-related deaths. These medicines include opioid analgesics, anxiolytics such as pregabalin and diazepam and antidepressants. This protocol outlines how a systematic review will be undertaken (during June 2021), which aims to examine the literature on the pattern of OTC and POM misuse among adults who are accessing substance misuse treatment services. It will include the types of medication being taken, prevalence and demographic characteristics of people who access treatment services.Methods and analysis An electronic search will be conducted on the Cochrane, OVID Medline, Pubmed, Scopus and Web of Science databases as well as grey literature. Two independent reviewers will conduct the initial title and abstract screenings, using predetermined criteria for inclusion and exclusion. If selected for inclusion, full-text data extraction will be conducted using a pilot-tested data extraction form. A third reviewer will resolve disagreements if consensus cannot be reached. Quality and risk of bias assessment will be conducted for all included studies. A qualitative synthesis and summary of the data will be provided. If possible, a meta-analysis with heterogeneity calculation will be conducted; otherwise, Synthesis Without Meta-analysis will be undertaken for quantitative data. The reporting of this protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses.Ethics and dissemination Ethical approval is not required. Findings will be peer reviewed, published and shared verbally, electronically and in print, with interested clinicians and policymakers.PROSPERO registration number CRD42020135216.